Virtual and Augmented Reality Technologies in the Healthcare System of the Arctic Regions of the Russian Federation - Lyudmila E. Khaymina; Larisa I. Zelenina; Evgeniy S. Khaymin; Svetlana I. Fedkushova (Арктика и Север)
Virtual and augmented reality, as one of the end-to-end technologies of the digital economy, currently has wide practical application in the field of healthcare, helping both doctors and patients. VR/AR technologies allow the most effective rehabilitation of patients with diseases of the musculoskeletal sys-tem, provide significant assistance in dealing with psychosomatic disorders, and can be used in surgical operations. In addition, virtual doctors and nurses can be used to provide medical care at home; existing VR applications allow for better involvement of patients in therapy. VR/AR solutions developed in close cooperation of doctors and IT specialists have great development prospects. The application of virtual and augmented reality technologies in the medical care system should result in improved quality of medical services, which is especially important for remote regions. The regions of the Arctic zone of the Russian Federation, being geographically distributed, remote areas with difficult natural and climatic conditions, set themselves the task of developing high-tech medical care to improve the quality of life of the population. It becomes important for regional medical institutions to study and apply the best practices of medical IT solutions based on VR/AR technologies.